Extensive burns complicated with heparin-induced thrombocytopenia: A report of two cases - Noriko Miyagawa; Motoo Fujita; Yu Kawazoe; Shigeki Miyata; Takuma Maeda; Shigeki Kushimoto (Elsevier, 2020)
Patients with tissue injury due to severe trauma are at an increased risk for heparin-induced thrombocytopenia (HIT). However, HIT and its incidence have not been evaluated in patients with extensive burns. We describe two cases of extensive burn injuries with HIT in an attempt to recognize the pathology and clinical significance of HIT in patients with extensive burn injuries.Case 1 was a woman in her 50 s with burn injuries (total burn surface area, 60%). On day 9, her platelet count decreased significantly, and she was positive for the anti-platelet factor-4 immunoglobulin (Ig)-G antibody. On day 22, catheter-related iliac vein thrombosis was diagnosed. Case 2 was a man in his 40 s with burn injuries (total burn surface area, 77%). On day 5, he was diagnosed as having cerebellar infarction. His platelet count decreased significantly, and he was positive for the anti-platelet factor-4 IgG antibody on day 9. His condition was also complicated with pulmonary thrombosis. In both patients, heparin was used only to maintain arterial catheter patency. In conclusion, physicians must consider the possibility of HIT as a cause of thrombocytopenia in patients with burn, and it is necessary to discontinue all heparin and administer non-heparin-anticoagulant when HIT is clinically suspected. Further evaluation of HIT in patients with burn injuries is required. Keywords: Heparin, Thrombosis, Heparin-induced thrombocytopenia antibodies, Extensive burn